Gandhi’s Philosophy of Life and The Rationality of his Nonviolence - Mishra, Prem Anand (Vidyapith (વિદ્યાપીઠ), 2024)
This paper examines Gandhi’s philosophy of life, with a focus on how nonviolence serves as both a method of inquiry and a framework for judgment. Although Gandhi’s life and philosophy are intertwined, this study aims to extract the fundamental aspects of his worldview, emphasizing the logic that underpins his dedication to nonviolence. Gandhi’s nonviolence is not merely an ethical stance, but a rational approach that informs his views on religion, society, history, economics, and politics. By interpreting nonviolence as a form of rationality, the paper contrasts Gandhi’s ideas with Max Weber’s forms of rationality to offer a deeper understanding of Gandhi’s unique perspective. Ultimately, Gandhi’s nonviolence emerges as both a rational and non-rational force, providing a holistic framework for interpreting his philosophy of life.